The Relationship Between Application Operational Procedure (SPO) of the Right Principle of Drug Administration with the Standard Level of Patient Satisfaction - Qurrotul Aeni; Nur Chasanah; Rina Anggraeni; Andriyani Mustika Nurwijayanti (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Patient satisfaction is a feeling of pleasure that is felt for hospitalized patients because getting optimal servicequality. In providing nursing services, Standard Procedure Operational (SPO) is very important to help nurses achieve a quality of nursing care. In giving the drug should pay attention to the six principles of right which has become a obligation procedure before it gave the drug, that is: right patient, right drug, right dose, right way, right time and right documentation. The purpose of this research to determine the relation between the six right principles implementation of Standard Procedures Operational (SPO) to dispense the drug with the level of patient satisfaction at Cempaka Lounge Dr. H. SoewondoHospital in Kendal. The research used a descriptive correlational design with cross sectional approach. Samples were taken by using Total Sampling number of 48 patients. Research tools using questionnaires then the data were analyzed by univariate and bivariate statistical test obtained chi square p value of 0.000 (p value<0.05). the SPO dispensing has good value amounted to 47.9%, which has a sufficient level of SPO Dispensing of 45.8%, and the rate of less Dispensing SPO only 6.3%. While a right level of patient satisfaction of 52.1%, which have high levels of 41,7%, and the level patient satisfaction of less only 6,3%. Recommendations result of this research is that nurses always apply SPO properly to improve patient satisfaction.